Perancangan Dan Implementasi E-Commerce Berbasis Web (Studi Kasus: Horn Music Merch Distro) - Hilman Yuliansyah (Jur. Teknologi Informasi Fak. Teknik UMY, 2016)

(untitled)
Horn Music Merch Sales Enterprises is one of the stores selling clothes, bags, and hats that have difficulties to promote its products, and easier for buyers to not shop immediately to the store sales. This shop need a web for facilitate sales. In this thesis designing a sales website with specification can display some product, price, delivery cost, total cost, and sales report. This sales information system is expected to become an alternative method in promotion and easier for purchase transactions, effective and efficient. This system focuses on the member (customer) and admin. Features that can be accessed by customers after registration and login namely the process of booking. The design is done using tool software Xampp. Making this sales system facilitate costumers in the process of purchasing and facilitate the shop owner in promoting their product more effectively and efficiently.